Social Innovation in Higher Education Landscape, Practices, and Opportunities - Păunescu, Carmen; Lepik, Katri-Liis; Spencer, Nicholas (Innovation, Technology, and Knowledge Management, 2022)
This open access book offers unique and novel views on the social innovation landscape, tools, practices, pedagogies, and research in the context of higher education. International, multi-disciplinary academics and industry leaders present new developments, research evidence, and practice expertise on social innovation in higher education institutions (HEIs), across academic and professional disciplines. The book includes a selected set of peer-reviewed chapters presenting different perspectives against which relevant actors can identify and analyse social innovation in HEIs. The volume demonstrates how HEIs can respond to societal challenges, support positive social change, and contribute to the development of international public policy discourse. It answers the question 'how does the present higher education system, in different countries, promote social innovation and create social change and impact'. In answering this question, the book identifies factors driving success as well as obstacles. Furthermore, it examines how higher education innovation assists societal challenges and investigates the benefits of effective social innovation engagement by HEIs. The interdisciplinary approach of the volume makes it a must-read for scholars, students, policy-makers, and practitioners of economics, education, business and management, political science, and sociology interested in a better understanding of social innovation.